The Implementation of Competitive Strategy at SDN Cipondoh to Achieve Competitive Advantage - Widyawati, Wiwik Yully; Hidayat, Rais (LPPM Universitas PGRI Semarang, 2024)
The aim of this research is to determine understanding of the implementation of competitive strategies at SDN in Cipondoh. This research was carried out at SD Negeri Cipondoh 1 Tangerang. . The method in this research is to use a descriptive qualitative method approach with study analysis of competitive strategies implemented at SD Negeri Cipondoh 1 Tangerang. The Technique of data collection uses interview which focus on school principals, teachers and student’s parents. The results of this research are SD N Cipondoh 1 has implemented a competitive strategy to achieve competitive advantage. This is proven by the strategic condition of the school, its vision and mission are clear, it has set goals correctly, formulated strategies well and precisely, and also implemented operational plans as a routine and planned evaluation and monitoring tool enabling rapid adaptation to environmental changes. An in-depth analysis of the implementation of competitive strategies at SD N Cipondoh 1 provides educators with useful information. In the midst of an increasingly competitive world of education, other schools can use this as a reference to improve their strategic operations. Therefore, it is important for this school and schools in Indonesia to maintain competitive advantage, the school must update strategies, manage resources well, and build superior and high-quality human resources. They must also build collaboration, a sense of mutual cooperation and create innovative or new learning environments.